HUKUM JINAYAH ANTARA APLIKASI DAN SEJARAH - Nurul Husna (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2017)
Indonesia is a predominantly Muslim country, with only 20 percent of the Indonesian population converting to other religions. When viewed from the majority of the population, should the enforcement of Islamic Law in Indonesia is more dominant than the national law, but when looking at law enforcement in Indonesia, The government took the initiative to follow the positive law taken from the Criminal Code (KUHP) and the Criminal Procedure Code (KUHAP) which if we explore the history is more inclined to the Dutch law. When looking at the application of punishment in Indonesia and then reconsidering the basic law that Allah has established from the Qur'an and Hadith, it is very contra if these two laws are combined. The application of law in Indonesia is as if only a legal provision resulted from deliberations of law enforcement and very far with the law established by Allah SWT in the Qur'an, So unknowingly, when the students discussed the basic law that refers to the Qur'an and Hadith, the law becomes just only information and becomes a science of history that can only be learned and can not be applied, the provision of God will continue to disappear in time, and only become memories For anyone who ever knew him especially in education.